Current and future development of thermal grids in Switzerland: an organizational perspective - Speich, Matthias; Chambers, Jonathan; Ulli-Beer, Silvia (Frontiers in Sustainable Cities, 2024)
Thermal grids are key to decarbonizing heating and cooling. However, their development is a complex socio-technical process. This study aims to 1) understand the thermal grid ecosystem's development under changing political, economic and cultural frame conditions, 2) elicit actors' perception of options for future development, and 3) identify concrete problem situations for the future development of thermal grids and describe how to address them. We draw on 18 semi-structured interviews with decisionmakers in utilities, municipal administrations, planning and engineering companies and intermediary organizations.With increased strategic importance of thermal grids, the ecosystem has been in a phase of rapid growth and professionalization in the last 10-15 years. This is reflected in a rapid increase in the number of grids, but also in capability and capacity building and greater quality standards. This transformation has been supported by a resource pool (e.g., knowledge base, capacities and capabilities, networks or decision-support tools), built partly through the value network's activities and partly through purposeful orchestration by associations, authorities, utilities and other actors. While policy developments, energy price fluctuations and changes in customer perceptions spurred demand, thermal grid development is limited by supply-side constraints, especially a skill shortage.Four interrelated problem situations were identified: 1) Municipalities lack the resources to manage the implementation of their energy strategies. 2) The modernization of thermal grids and integration of lowcarbon heat sources entails high transaction costs. 3) The implementation of thermal grids is subject to delays and quality risks, with consequences for the timely achievement of decarbonization goals. 4) Customers face uncertainty on available options, as well as on the systemic impacts of their decisions.Based on current practices, suggestions by the interviewees, as well as a comparison with the international literature, we identify four development areas to address these problem situations: 1) Empower and support municipalities. 2) Manage the scarcity of qualified workforce. 3) Leverage digital technology for the planning, realization and operation of thermal grids. 4) Pilot technological and organizational innovations together. This complements the set of previously suggested measures to support the development of thermal grids, which focused strongly on technical and regulatory aspects.